Embriologia de Stifftia chrysantha J. C. Mikan e S. fruticosa (Vell.) D. J. N. Hind & Semir e suas implicações na sistemática dos grupos basais de Asteraceae - Bonifacio, Stephani Karoline de Vasconcelos (2015)
(Embryology of Stifftia chrysantha J. C. Mikan and S. fruticosa (Vell.) D. J. N. Hind & Semir and its implications to the systematic of early divergent Asteraceae) - Researches focusing on embryological features are important to the understanding of phylogenetic relationships because they are more conservatives and less susceptible to phenotypic changes. Embryological studies in basal groups are significant because they increase the knowledge about taxa, contributing to the comprehension about their diversity, biology, evolution and conservation. Thus, Stifftia chrysantha J. C. Mikan and S. fruticosa (Vell.) D. J. N. Hind & Semir were chosen, due their distribution and position within Asteraceae, specially because both genus and tribe present disagreement between molecular and morphological data, contributing with information for future comparative studies. The material was collected and processed according to usual techniques of light and scanning electron microscopy. The species are homogenous and exhibit embryological data common to Asteraceae members like secretory tapetum and Polygonum megagametophyte. However, the anther wall development of the basic type, bicelled pollen grains, ovule vascularization that extends just to chalaza, obturator presence, parenchimatic pericarp with non prominent ribs, strophiolate seed with trichomes on funicule, differentiate the genus from among Asteraceae members and indicate potencial plesiomorphic characters for the family.